Development and Validation of a Stability-Indicating HPLC Method for the Simultaneous Determination of trans-Resveratrol and cis-Resveratrol in an Injectable Solution - Esmeralda Mota-Lugo; Mariana Dolores-Hernández; Elvia A. Morales-Hipólito; Iris A. Blanco-Alcántara; Hugo Cuatecontzi-Flores; Raquel López-Arellano (Journal of Analytical Methods in Chemistry)
trans-Resveratrol, a phytochemical compound with antioxidant power and various therapeutic effects, such as cardioprotective, chemopreventive, and neuroprotective, among others, has disadvantages of poor solubility and limited stability, creating difficulties for the development of new strategies for its quantification. This study developed and validated an analytical stability method for trans-resveratrol by high-pressure liquid chromatography with photodiode-array detection (HPLC-PDA), which allowed its quantification in the presence of its degradation products. The quantification of trans-resveratrol occurred at a retention time of 2.6 min, with ammonium formate (10 mM, pH = 4)/acetonitrile, 70/30 v/v, as mobile phase. The validation met the ICH Q2 criteria of specificity, method linearity (2.8–4.2 μg/ml), precision and accuracy, robustness, quantification limit (0.176 μg/ml), and detection (0.058 μg/ml). As degradation products, cis-resveratrol was observed at 3.9 min, which could be resveratrone in 3.2 min and five unidentified products in 0.7, 1.0, 1.4, 1.8, and 5 min. Some solutions subjected to temperature stress of 40 and 60°C, UV light, and acidic and basic hydrolysis exhibited colour changes. An analytical method was obtained by HPLC-PDA, which allowed quantifying the stability of trans-resveratrol in a fast and specific manner in the presence of its degradation products.